High-Fat Diet and Short-Term Unpredictable Stress Increase Long-Chain Ceramides Without Enhancing Behavioral Despair - Sambolín-Escobales, Lubriel; Tirado-Castro, Lizmarie; Suarez, Cristina; Pacheco-Cruz, Dariangelly; Fonseca-Ferrer, Wilfred; Deme, Pragney; Haughey, Norman; Chompre, Gladys; Porter, James T. (Frontiers in Molecular Biosciences, 2022)
Clinical and preclinical studies suggest that increases in long-chain ceramides in blood may contribute to the development of depressive-like behavior. However, which factors contribute to these increases and whether the increases are sufficient to induce depressive-like behaviors is unclear. To begin to address this issue, we examined the effects of high-fat diet (HFD) and short-term unpredictable (STU) stress on long-chain ceramides in the serum of male and female rats. We found that brief exposure to HFD or unpredictable stress was sufficient to induce selective increases in the serum concentrations of long-chain ceramides, associated with depression in people. Furthermore, combined exposure to HFD and unpredictable stress caused a synergistic increase in C16:0, C16:1, and C18:0 ceramides in both sexes and C18:1 and C24:1 in males. However, the increased peripheral long-chain ceramides were not associated with increases in depressive-like behaviors suggesting that increases in serum long-chain ceramides may not be associated with the development of depressive-like behaviors in rodents..